Numerical Solution of Integral-Algebraic Equations with Weakly Singular Kernels by k−step Methods - M.V. Bulatov (Известия Иркутского государственного университета: Серия "Математика", 2015)
In this paper we describe numerical methods for solution integral-algebraic equations wiht weakly singular kernels. Methods are based on explicit Adam’s methods, product integration methods for the integral part and on extrapolation formulas for the main part of the equation are proposed. We got weights of quadrature formulas. Presented results of numerical experiments.